Dietary inflammatory index and inflammatory biomarkers in adolescents from LabMed physical activity study - Almeida-de-Souza, Juliana (2020)
Background/objectives The dietary inflammatory index (DII) is a tool to measure the diet’s inflammatory potential and has been used with adults to predict low-grade inflammation. The present study aims to assess whether this dietary score predicts low-grade inflammation in adolescents. Subjects/methods The sample comprises 329 adolescents (55.9% girls), aged 12–18 years, from LabMed Physical Activity Study. DII score was calculated based on a food-frequency questionnaire and categorized into tertiles. We collected blood samples to determine the follow inflammatory biomarkers: C-reactive protein (CRP), interleukin-6 (IL-6), complement component 3 (C3), and 4 (C4). In addition we calculated an overall inflammatory biomarker score. Odds ratios (OR) and 95% confidence intervals (95%CI) were computed from binary logistic regression models. Results DII score, comparing first with third tertile, was positively associated with IL-6 in crude model (OR = 1.88, 95% CI:1.09–3.24, ptrend = 0.011) and in fully adjusted (for biological and lifestyle variables) (OR = 3.38, 95%CI:1.24–9.20, ptrend = 0.023). Also, DII score was positively associated with C4, when fully adjusted (OR = 3.12, 95%CI:1.21–8.10, ptrend = 0.016). DII score was negatively associated with C3 in crude model, comparing first with second but not with third tertile, and no significant associations in fully adjusted model were observed, although a trend was found (OR = 1.71, 95% CI:0.63–4.66, ptrend = 0.044). No significant associations were observed between DII score and CRP. However, DII score was positively associated with the overall inflammatory biomarker score, when fully adjusted (OR = 5.61, 95% CI:2.00–15.78, ptrend = 0.002). Conclusions DII score can be useful to assess the diet’s inflammatory potential and its association with low-grade inflammation in adolescents.